Analysis of Inorganic Waste Material Flow for Zero Waste Achievement Scenarios on the Mataram University Campus - Annisa Annisa; Suripto Suripto; Astrini Widiyanti; Ernawati Ernawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Waste management at the University of Mataram still uses the traditional scenario, namely collecting, transporting and disposing of it at the landfill so that it has not made a real contribution to reducing waste generation in Mataram City. This study aimed to determine the generation, composition, and potential for reducing inorganic waste on the Mataram University campus. Data on inorganic waste generation and its composition were collected using the load count method according to ASTM D5231-92 and SNI 19-3964-1994. The data were then processed through Material Flow Analysis (MFA) with the 3R approach. The results showed that the inorganic waste generated on the Mataram University campus reached 431.09 kg/day (0.0208 kg/person/day), and after being collected by scavengers (average 149.09 kg/day), residue of 282.01 kg/day (65.43%) was left, with the composition dominated by paper (32.78%) and plastic (32.40%). The potential for reducing inorganic waste per day reached 186.43 kg, namely through reduce (86.8 kg), recycle (98.81 kg), and reuse (0.82 kg), leaving a residue of 95.59 kg (22.17%). The new scenario for waste management with the implementation of the 3Rs approach can significantly reduce the generation of inorganic waste, thereby supporting efforts to achieve zero waste on the Mataram University campus.